Information systems architecture and technology. proceedings of 37th International Conference on Information Systems Architecture and Technology – ISAT 2016 /: proceedings of 37th International Conference on Information Systems Architecture and Technology – ISAT 2016. Part II : (2017) - Unknown
No abstract available